Association of eHealth Literacy With Colorectal Cancer Knowledge and Screening Practice Among Internet Users in Japan - Mitsutake, Seigo; Shibata, Ai; Ishii, Kaori; Oka, Koichiro (JMIR Publications, 2012)
BackgroundIn rapidly developing Internet-user societies, eHealth literacy has become important in promoting wellness. Although previous studies have observed that poor health literacy is associated with less knowledge and screening practice of colorectal cancer (CRC), little is known about whether eHealth literacy is associated with these variables. ObjectiveThe present study examined associations between eHealth literacy, knowledge of CRC, and CRC screening practices. MethodsData were analyzed for 2970 Japanese adults (men, 49.9%; mean age ± SD, 39.7 ± 10.9 years) who responded to an Internet-based cross-sectional survey. Knowledge of the definition of CRC, its risk factors and screening practice, previous experience of CRC screening, score on the Japanese version of the eHEALS (J-eHEALS), sociodemographic attributes (sex, age, marital status, educational attainment, and household income level), and frequency of Internet usage were obtained. Sociodemographic attributes and frequency of Internet usage were used as control variables in the multiple regression and logistic regression models. ResultseHealth literacy was positively associated with CRC knowledge (β = .116, < .001), when the covariables of both eHealth literacy and CRC knowledge were used in the multiple regression model. Moreover, after controlling for sociodemographic factors, which were significantly associated with eHealth literacy and CRC screening practice, an increase of 1 point in the eHEALS score signified that participants were 1.03 times (95% CI = 1.01-1.05) more likely to undergo CRC screening. ConclusionsInternet users with high eHealth literacy are more likely to have knowledge and previous screening practice related to CRC compared to those with low eHealth literacy.